Teaching Atwood's The Handmaid's Tale with Sidhwa's Cracking India as Introduction to Transnational Feminisms - Lovrod, Marie (Atlantis, 2006)
The Handmaid's Tale and Cracking India provide a context for introducing second-year students to transnational feminisms. Students with wide-ranging preparation engaged the critiques and "horizons of possibility" that transnational feminisms propose, grounding their work in the perspectives each novel illuminates, considered in tandem.